One-step Synthesis of Biomass-Based Carbon Dots for Detection of Metal Ions and Cell Imaging - Huang, Xiaolin; Liu, Jiaheng; Zhao, Bin; Bai, Yibing; Peng, Zhibin; Zhou, Jundan; Wang, Chenxi; Zhao, Xuan; Han, Shiyan; Zhang, Chunlei (Frontiers in Energy Research, 2022)
Biomass-based carbon dots (Bio-CDs) were prepared from dehydroabietic acid using a one-step hydrothermal process. Characterization by TEM, XPS and FTIR spectroscopy showed that the Bio-CDs are spherical nanoparticles containing mainly C, N and O elements, with functional groups such as amino and carbonyl groups on their surface. The optical properties of the Bio-CDs were studied in detail. A solution of Bio-CDs exhibited excitation-dependent blue fluorescence emission. The solution showed excellent photostability under ultraviolet light and the fluorescence intensity could be enhanced by decreasing the temperature. The intensity of fluorescence emission of the solution was essentially unchanged over the pH range 3.91–8.69, and in the presence of different anions and cations, other than Fe3+ and Pb2+. Fe3+ and Pb2+ ions, respectively, quenched and enhanced the intensity of the fluorescence emission of the solution, allowing sensitive and selective detection of Fe3+ (LOD = 2.33 μM, Em = 437 nm) and of Pb2+ (LOD = 0.27 μM, Em = 437 nm and LOD = 0.33 μM, Em = 500 nm). As a further demonstration of potential applications, the Bio-CDs were shown to have low cytotoxicity and to stain cell nuclei as effectively as the commonly used nuclear stain 4′,6-diamino-2-phenylindole (DAPI), demonstrating their promise in the field of cell imaging.